2007
DOI: 10.1111/j.1553-2712.2007.tb01808.x
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Common Ground: Developing Emergency Medicine in Iran

Abstract: Academic ties between Iran and the United States were extensive before the 1979 revolution in Iran. After 20 years of negligible academic exchanges, there has been a growing trend of professional contacts between the two countries over the past few years. The genuine warmth of friendship and commitment to excellence in emergency medicine (EM) among Iranians has transcended the political barriers to allow international contribution of EM development in the country. Since 1999, there has been a successful academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Few LMIC have specialists in emergency medicine, and in many countries this is not recognized as a specialty of its own. 7 The specialty was developed in Iran in 2000 39 and graduated EMPs have been involved in providing trauma care for several years. The findings of our study showed that the EMPs have improved the delivery of trauma care in their own ED.…”
Section: Discussionmentioning
confidence: 99%
“…Few LMIC have specialists in emergency medicine, and in many countries this is not recognized as a specialty of its own. 7 The specialty was developed in Iran in 2000 39 and graduated EMPs have been involved in providing trauma care for several years. The findings of our study showed that the EMPs have improved the delivery of trauma care in their own ED.…”
Section: Discussionmentioning
confidence: 99%
“…The high numbers of formally educated staff in Iran make it possible to develop a comprehensive educational plan for pre-hospital trauma care and to link staff's education and reality (practice) by implementing evidence-based training courses. This can be done by the help of Emergency Medicine Specialists who are perceived to have had an important role in improving the quality of trauma care in recent years [38]. Training staff in BLS, such as Pre-hospital Trauma Life Support (PHTLS) program [8,31,32] and providing EMT certification [37] have proven to be effective in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no clear policy currently outlined by Iran to handle the issue of ED crowding. Current policies have focused on the development of EM in the country: increasing the number of EDs, the number of EM residency programs, and the number of EM‐trained physicians practicing in the ED 46 . The current goal is to increase Iran’s ED capacity and capabilities.…”
Section: Iranmentioning
confidence: 99%